PENGARUH MODEL PEMBELAJARAN LITERASI ORIENTASI KOLABORASI DAN REFLEKSI (LOK-R) TERHADAP KEMAMPUAN LITERASI NUMERASI SISWA PADA MATERI STATISTIKA - Wisi Marita; Widiawati; Reza Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the influence of the LOK-R learning model on students' numeracy literacy ability in statistical material in class X. The research method used is quantitative, True Experiment Design type, with a Pretest-Posttest Control Group Design. The sample of this study consists of two classes, namely the experimental class that uses the LOK-R learning model and the control class that uses the conventional learning model. The research instruments are in the form of pre-test and post-test tests. The results showed that there was a significant increase in numeracy literacy skills in the experimental class compared to the control class. The average post-test score of students in the experimental class was 72% higher than that of the control class of 53%. These results prove that the application of the LOK-R learning model is effective in improving students' numeracy literacy skills.